Cassandra Mordini: capstone - Mordini, Cassandra, artist (Colorado State University. Libraries, 2015)
The artist's statement: My work tends to have a clean graphic style. Color is my favorite element to work with. It really fulfills my branding pieces. In particular, the Pupbles pieces have specific colors that coordinate with each different type of packaging. I used the modern colors of teal and orange for the Midtown project in order to attract a younger generation to the area. I try to focus on marketing concepts when creating my pieces. It is important for the product to be desirable to the majority of people for it to sell. In projects that do not involve sales, my concept is strong. For example, my Alice's Adventures in Wonderland piece, the Cheshire Cat is represented by a smile but in the silhouette of a cat facing backwards. This is a twist on the traditional representation of only a smiling cat. The idea comes across but with a more dynamic approach. Color and concept are the focuses of my work as a whole.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.